Modifying Science Activities and Materials to Enhance Instruction for Students with Learning and Behavioral Problems - Christine K. Ormsbee; Kevin D. Finson (Intervention in School and Clinic, 2000)
Most science educators report a willingness to teach students with learning and behavioral differences; however, they often also indicate having limited information about how to make the science classroom more accessible. One avenue of support is the modification of science instructional materials in order to reduce barriers that may exist as a result of poor reading, organization, or work-completion skills. Some suggestions for instruction modifications are provided in this article. Also included is a sample science activity that was redesigned to support students with learning and behavioral concerns.